Green Synthesis of Feather-Shaped MoS2/CdS Photocatalyst for Effective Hydrogen Production - Yang Liu; Hongtao Yu; Xie Quan; Shuo Chen (International Journal of Photoenergy)
MoS2/CdS photocatalyst was fabricated by a hydrothermal method for H2 production under visible light. This method used low toxic thiourea as a sulfur source and was carried out at 200°C. Thus, it was better than the traditional methods, which are based on an annealing process at relatively high temperature (above 400°C) using toxic H2S as reducing agent. Scanning electron microscopy and transmission electron microscopy images showed that the morphologies of MoS2/CdS samples were feather shaped and MoS2 layer was on the surface of CdS. The X-ray photoelectron spectroscopy testified that the sample was composed of stoichiometric MoS2 and CdS. The UV-vis diffuse reflectance spectra displayed that the loading of MoS2 can enhance the optical absorption of MoS2/CdS. The photocatalytic activity of MoS2/CdS was evaluated by producing hydrogen. The hydrogen production rate on MoS2/CdS reached 192 μmol·h−1. This performance was stable during three repeated photocatalytic processes.